1983
DOI: 10.6028/nbs.sp.647p1
|View full text |Cite
|
Sign up to set email alerts
|

The economic effects of fracture in the United States

Abstract: The final report describes the input/output methodology used to estimate the total, presently reducible and future reducible costs of fracture, and the supplemental models used to establish the direct and indirect (including the costs of death, pain, and suffering from injury and environmental degradation) costs arising from fracture occurrence. Discussion of guidelines used to estimate these costs (e.g., "row rules") is amply provided. A complete set of the input/output tables was generated by BCL for this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 2 publications
0
26
0
3
Order By: Relevance
“…Reviews both in the USA and Europe [1,2] indicate that in-service breakage of engineering structures and components costs around 4% of GNP in industrialised nations, the price which has to be paid becoming socially unacceptable whenever failures result in loss of human lives. In this complex scenario, one of the most difficult challenges faced by the metalworking sector is improving the in-service performance of structural assemblies by limiting not only the weight, but also the associated production, maintenance and energy costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviews both in the USA and Europe [1,2] indicate that in-service breakage of engineering structures and components costs around 4% of GNP in industrialised nations, the price which has to be paid becoming socially unacceptable whenever failures result in loss of human lives. In this complex scenario, one of the most difficult challenges faced by the metalworking sector is improving the in-service performance of structural assemblies by limiting not only the weight, but also the associated production, maintenance and energy costs.…”
Section: Introductionmentioning
confidence: 99%
“…
On th e u s e o f lin e ar-e las tic lo cal s tre s s e s to d e s ign lo a d -carryin g fille t-w e ld e d s te e l jo in ts again s t s tatic lo ad in g
IN TROD U CTIONReviews both in the USA and Europe [1,2] indicate that in-service breakage of engineering structures and components costs around 4% of GNP in industrialised nations, the price which has to be paid becoming socially unacceptable whenever failures result in loss of human lives. In this complex scenario, one of the most difficult challenges faced by the metalworking sector is improving the in-service performance of structural assemblies by limiting not only the weight, but also the associated production, maintenance and energy costs.

With regard to the technological issues involved in the manufacturing process, it is well-known that a challenging aspect of making high-performance structures and components is efficiently joining Please, cite this paper as: Ameri, A.

…”
mentioning
confidence: 99%
“…If the constants in the MWCM are calibrated using fatigue curves generated under fully-reversed uniaxial (ρeff=1) and torsional (ρeff=0) cyclic loading, relationships (2) and (3) can be rewritten as follows [44]:…”
Section: Fundamentals Of the Mwcmmentioning
confidence: 99%
“…Reviews both in the USA and Europe have indicated that in-service cracking of components costs around 4% of GNP in industrialised nations [2,3]. Above and beyond the economic cost of fatigue failure, there is often an associated and socially unacceptable cost in terms of loss of human life.…”
Section: Introductionmentioning
confidence: 99%
“…This can be ascribed to the presence of stress/strain concentration phenomena occurring at the contact surface and with the local multiaxial stress/strain fields rapidly decaying from the surface inward [2,3]. Reviews both in the USA and in Europe [4,5] indicate that in-service breakage of structural components costs around 4% of GNP in industrialized nations, 50% to 90% of failures being caused by fatigue. In this scenario, fretting fatigue is always a matter of concern to structural engineers since it can remarkably reduce the in-service lifetime of important structural parts such as, for example, threaded pipe connections, bolted/riveted joints, blade-disk attachments in gas/steam turbines, shrink-fitted shaft, and aero-engine splined couplings.…”
Section: Introductionmentioning
confidence: 99%